1974
DOI: 10.2307/2347055
|View full text |Cite
|
Sign up to set email alerts
|

A Note on the Analysis of Gap-Acceptance in Traffic

Abstract: Summary In a recent paper, Ashton (1971) has proposed two methods for the analysis of gap‐acceptance data. It is not clear what parameters of driver behaviour and of the distribution of offered gaps are being estimated in these two methods. A model is proposed for the gap‐acceptance behaviour of drivers. Using this model it is shown that the asymptotic values of Ashton's estimators are functions of both the parameters describing driver behaviour and those describing the stream of offered gaps. Consequently it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The study found that Ashworth method and maximum likelihood technique gave satisfactory results. Miller (1974) further developed a model incorporating real life situations like driver entering into the intersection while considering his lag, inconsistent driver, variation in gap acceptance behavior with age and gender of drivers and type of vehicle. The parameters of the model were estimated using maximum likelihood method.…”
Section: Background Literaturementioning
confidence: 99%
“…The study found that Ashworth method and maximum likelihood technique gave satisfactory results. Miller (1974) further developed a model incorporating real life situations like driver entering into the intersection while considering his lag, inconsistent driver, variation in gap acceptance behavior with age and gender of drivers and type of vehicle. The parameters of the model were estimated using maximum likelihood method.…”
Section: Background Literaturementioning
confidence: 99%
“…In early 1980's, researchers developed gap acceptance models by comparing existing methods of critical gap estimation and obtained satisfactory results using Ashworth method (Miller, 1972) and maximum likelihood technique (Miller, 1972;1974). Later, binary logit model was developed (Hamed et al, 1997) to determine the drivers gap acceptance probabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, in the United Kingdom-UK where vehicles observe the left hand rive rule just like in South Africa, linear regression is the most commonly used predictive model because it has inbuilt substantive geometric sensitivity and a correction factor for entry radius and entry angles. It has been shown in previous studies [12] that the linear relationship between entry and circulating flows can be modelled with equations 9 and adjusted with equation 10 according to Kimber [14]. Where; Q e = entry flow rate (pcu/h); Q c = circulating flow rate (pcu/h), F is the intercept and fc is the slope Consider equation 12 again, when it rains, a dummy variable (ε) is introduced to depict that condition hence 1, otherwise zero for dry weather.…”
Section: (7)mentioning
confidence: 99%